Diagnostic Performance of Rapid Antigen Tests to Detect Equine Rotavirus A - Ann Cullinane; Maura Nelly; Laura Dayot; Gabija Lukaseviciute; Marie Garvey; Jennifer Healy; Robert Gallagher (Viruses)
This study describes a comparison of the detection of rotavirus in clinical samples from foals using two commercially available rapid antigen detection (RAD) kits, with the detection of rotavirus nucleic acid via a laboratory-based, in-house, real-time reverse transcription polymerase chain reaction (RT-PCR) assay. One hundred and forty freeze-thawed samples (70 that were RT-PCR-positive and 70 that were RT-PCR-negative on original tests) submitted to the diagnostic laboratory over a seven-year period were tested in addition to 123 fresh samples (15 RT-PCR-positive and 108 RT-PCR-negative) submitted over a four- month period in 2024. The analyst performing the RAD tests was blinded to the RT-PCR result as were the two individuals who read the results. Samples with discordant results were re-tested in duplicate using RT-PCR and the two RAD kits. Both kits demonstrated a high level of concordance with the RT-PCR (>95%). However, testing of serial dilutions of RT-PCR positive faeces samples indicated that the RADs failed to detect the virus at the higher dilutions. In conclusion, the RADs evaluated are potentially useful for screening individual foals and for the determination of the urgency of the appropriate treatment and isolation. Negative samples from suspect cases and weak positives should always be submitted to a specialist laboratory for real-time RT-PCR testing.